Productive infection of isolated human alveolar macrophages by respiratory syncytial virus. - Panuska, J R (1990)
Respiratory syncytial virus (RSV) is a significant cause of lower respiratory tract disease in children and individuals with cell-mediated immunodeficiencies. Airway epithelial cells may be infected with RSV, but it is unknown whether other cells within the lung permit viral replication. We studied whether human alveolar macrophages supported RSV replication in vitro. Alveolar macrophages exposed to RSV demonstrated expression of RSV fusion gene, which increased in a time-dependent manner and correlated with RSV protein expression. RSV-exposed alveolar macrophages produced and released infectious virus into supernatants for at least 25 d after infection. Viral production per alveolar macrophage declined from 0.053 plaque-forming units (pfu)/cell at 24 h after infection to 0.003 pfu/cell by 10 d after infection and then gradually increased. The capability of alveolar macrophages to support prolonged RSV replication may have a role in the pulmonary response to RSV infection.